2009
DOI: 10.1007/s00540-009-0790-z
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic M1, M2, and A1 receptors play roles in tetanic fade induced by pancuronium or cisatracurium

Abstract: The tetanic fades produced by pancuronium and cisatracurium depend on the activation of presynaptic inhibitory M2 receptors; these agents also have anticholinesterase activities. The fades induced by these agents also depend on the activation of presynaptic inhibitory A1 receptors through the activation of stimulatory M1 receptors by acetylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 12 publications
3
24
1
Order By: Relevance
“…These data indicate that a higher activation of M 1 receptors on motor nerve by acetylcholine might be occurring in the cisatracurium-induced 100% Fade. It has already been demonstrated that A-value is influenced by presynaptic M 1 receptors activity when the motor nerve is stimulated at 50.00 Hz trains (Oliveira, Timóteo & Sá, 2002 cisatracurium-induced Fade would be the expected effect when the preparations were previously treated with ZM241385 (Oliveira et al, 2002;Pereira et al, 2012), it was supposed that the anticholinesterase activity of cisatracurium (Bornia et al, 2009;Bornia et al, 2011;Pereira et al, 2011) in the experimental condition causing 100% Fade reduced the expression of facilitatory effect induced by the blockade of A 2A receptors by producing a level of M 1 /M 2 activation by acetylcholine higher than that determined by the separate treatment of preparations with cisatracurium. Indeed, the previous treatment of preparations with ZM241385 caused a reduction in the A-value induced by cisatracurium which was not significantly (p > 0.05) different from that obtained after the administration of cisatracurium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These data indicate that a higher activation of M 1 receptors on motor nerve by acetylcholine might be occurring in the cisatracurium-induced 100% Fade. It has already been demonstrated that A-value is influenced by presynaptic M 1 receptors activity when the motor nerve is stimulated at 50.00 Hz trains (Oliveira, Timóteo & Sá, 2002 cisatracurium-induced Fade would be the expected effect when the preparations were previously treated with ZM241385 (Oliveira et al, 2002;Pereira et al, 2012), it was supposed that the anticholinesterase activity of cisatracurium (Bornia et al, 2009;Bornia et al, 2011;Pereira et al, 2011) in the experimental condition causing 100% Fade reduced the expression of facilitatory effect induced by the blockade of A 2A receptors by producing a level of M 1 /M 2 activation by acetylcholine higher than that determined by the separate treatment of preparations with cisatracurium. Indeed, the previous treatment of preparations with ZM241385 caused a reduction in the A-value induced by cisatracurium which was not significantly (p > 0.05) different from that obtained after the administration of cisatracurium.…”
Section: Resultsmentioning
confidence: 99%
“…This effect of atropine might be determined by the ability of the drug to reduce the action of acetylcholine on the presynaptic inhibitory-M 2 muscarinic receptors when the motor nerve is being stimulated at tetanizing frequencies (Prado et al, 1987). On the other hand, it has been shown that cisatracurium, an antinicotinic muscular relaxant agent that exhibits anticholinesterase activity in its molecules at clinical concentration (Bornia et al, 2009), also causes Fade in the phrenic nerve diaphragm muscle preparations of rats, but the Fade caused by the agent is not mediated by presynaptic inhibitory-M 2 receptors. In fact, Fade caused by cisatracurium seems to depend more on the activation of facilitatory-M 1 and facilitatory-A 2A adenosine receptors than on activation of presynaptic inhibitory-M 2 receptors on motor nerve (Bornia et al, 2009;Bornia et al, 2011;Pereira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other mechanisms, besides the blockade of neuronal nicotinic receptors, seem to be involved with the development of fatigue, as shown in muscle-phrenic nerve preparation. Among them, there are the facilitator action of type 1 muscarinic receptors (M1) and/or inhibitory action of type 2 (M2) 9 . In clinical monitoring this fatigue is characterized by TOF < 0.9 2,10,11 .…”
Section: Sugammadex: New Questions On Reversalmentioning
confidence: 99%